If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(2t + 8) = -108 Reorder the terms: -6(8 + 2t) = -108 (8 * -6 + 2t * -6) = -108 (-48 + -12t) = -108 Solving -48 + -12t = -108 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + -12t = -108 + 48 Combine like terms: -48 + 48 = 0 0 + -12t = -108 + 48 -12t = -108 + 48 Combine like terms: -108 + 48 = -60 -12t = -60 Divide each side by '-12'. t = 5 Simplifying t = 5
| 43+x=-37 | | x^4+5x^3-x^2-12x-6=0 | | 7x+21=3x+1 | | -6(27+8)=-108 | | b-38=-28 | | -3x^2+9x=2 | | 3(1.5+5y)=30 | | -6(27+8)=-180 | | 3(1+5y)=30 | | -11z=99 | | 2log(x)-Log(4)=Log(x+15) | | 3(5.0+5y)=30 | | 3/5÷2/5 | | 2p+q=15 | | h-47=-19 | | s/5=-30 | | 8+f=3 | | 17-2y=41 | | -10(s+2)=56 | | y+x=x*2.37500 | | y+x=x*z | | yz=-63 | | -8+9+5= | | 5z-10z=30 | | 4x+92=180 | | 1.8*10^16/2*10^8= | | y=600+100x-100lnx | | 65t^4-256= | | z=2z-y | | -7n+14=-5n-4 | | (-3x+5)(x-6)=0 | | (p-8)2=13 |